2020
DOI: 10.1002/hyp.13683
|View full text |Cite
|
Sign up to set email alerts
|

Recharge seasonality based on stable isotopes: Nongrowing season bias altered by irrigation in Nebraska

Abstract: The sustainability of groundwater resources for agricultural and domestic use is dependent on both the groundwater recharge rate and the groundwater quality. The main purpose of this study was to improve the understanding of the timing, or seasonality, of groundwater recharge through the use of stable isotopes. Based on 768 groundwater samples collected from aquifers underlying natural resources districts in Nebraska, the isotopic composition of groundwater (δ2H and δ18O) was compared with that of precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
2
4
0
1
Order By: Relevance
“…47 Preferential cold-season groundwater recharge has also been demonstrated for unirrigated systems in the Nebraskan agricultural plains. 48 Preferential cold-season groundwater recharge in this study was supported by the tile water isotopic composition, which reflected the 2014−2018weighted average precipitation and seasonal-weighted average precipitation (Figures 3 and 4). Water travel time to the tile drain (∼75 cm) was shorter than travel times to groundwater, which is why the average tile water δ 18 O and δ 2 H values were similar to the 2014−2018 weighted average precipitation and 2018 weighted average growing season precipitation values.…”
Section: Discussionsupporting
confidence: 54%
“…47 Preferential cold-season groundwater recharge has also been demonstrated for unirrigated systems in the Nebraskan agricultural plains. 48 Preferential cold-season groundwater recharge in this study was supported by the tile water isotopic composition, which reflected the 2014−2018weighted average precipitation and seasonal-weighted average precipitation (Figures 3 and 4). Water travel time to the tile drain (∼75 cm) was shorter than travel times to groundwater, which is why the average tile water δ 18 O and δ 2 H values were similar to the 2014−2018 weighted average precipitation and 2018 weighted average growing season precipitation values.…”
Section: Discussionsupporting
confidence: 54%
“…Data from wells far from the canals indicated that shallow groundwater was more likely influenced by local irrigation practices (i.e., furrows in fields), while deeper groundwater was impacted by both localized irrigation and canal leakage (Böhlke et al, 2007). Shallow groundwater in the Dutch Flats area has stable isotope composition consistent with surface water sources (i.e., North Platte River; (Böhlke et al, 2007;Cherry et al, 2020)).…”
Section: Site Descriptionsmentioning
confidence: 98%
“…Inicialmente, é necessário calcular a média ponderada da composição isotópica da precipitação em uma determinada estação (Equação 2) e, posteriormente, a proporção entre as contribuições para as recargas em uma estação ou outra (Equação 3) (JASECHKO et al 2014, JASECHKO & TAYLOR 2015, JASECHKO et al 2017, SANCHÉZ-MURILLO et al 2017, CHERRY et al 2020):…”
Section: Isótopos Estáveis Nas áGuas Subterrâneasunclassified